A Study of the Needs and Use of Information Technology to Enhance Cyber security Awareness of Elementary Students - Thongsak, Pornpana; Khlaisang, Jintavee (An Online Journal of Education, 2024)
The aims of this study were to: 1) explore current information technology usage among elementary students 2) study the user experience of mobile applications, and 3) identify the requirements of mobile applications to enhance cybersecurity awareness among elementary students. The sample group consisted of 400 upper elementary students. The research tool consisted of a questionnaire comprising checklist, ranking, and rating scale questions. Data were analyzed using frequency, percentage, mean, and standard deviation. The Modified Priority Need Index (Modified PNI) technique was utilized to prioritize needs. The research revealed the following insights 1) most elementary students used Android mobile phones to access the Google Chrome browser, 2) the overall user experience of mobile applications was rated at a high level, with setting a password to secure mobile applications having the highest average score, and 3) the need for mobile applications to enhance cybersecurity awareness among elementary students as a whole was determined to be at a high level. Thus, using technology in everyday life has the highest index of needs, followed by the use of technology for learning, and the use of social media, respectively.